The Effect of Trust, Digital Marketing And Service Quality To Customer Loyality Through Customer Satisfaction Perfume Product in Aliyanjaa Online Shop at DKI Jakarta - Aliya Mulahela; Resti Hardini (Universitas Negeri Semarang, 2023)
Aliyanjaa online experiences fluctuations which tend to continue to decline. In January 2019 there were 20 thousand subscribers, in December 2020 there were 10 thousand subscribers, in December 2021 there were 10 thousand subscribers, until in July 2022 there were only 5 thousand subscribers. This thesis research uses quantitative methods, with data collection techniques using questionnaires. The data measurement technique uses a Likert scale. Data analysis using SEM AMOS. In this questionnaire research which distributed 110 questionnaires to customers of perfume products at the Aliyanjaa online shop, it has been interpreted that there is an effect of trust, Digital Marketing, and service quality on customer loyalty through customer satisfaction for perfume products at the Aliyanjaa online shop.